Appendix

A.1. Derivation of ENU ($A$,$E$) to equatorial XYZ ($H$,$\delta$)


In [ ]:
import numpy as np
import matplotlib.pyplot as plt
%matplotlib inline
from IPython.display import HTML 
HTML('../style/course.css') #apply general CSS

We have seen in $\S$ 2.13 ➞, three main spherical trigonometry relationships between angles and arcs in a spherical triangle. Applying each of these equations, we will derive the equation A used in $\S$ 4.1 ➞.

Let's start from Figure 4.1.3, dislayed in $\S$ 4.1 ➞. We will consider the following spherical triangle STZ (as in Figure A1 right). From $\S$ 2.13 ➞, we have the following relationships:

  • The spherical cosine rule (Rule i): $\quad \quad \cos b = \cos a \cos c + \sin a \sin c \cos \hat{B}$
  • The spherical sine rule (Rule ii): $\quad \quad \; \; \: \sin b \sin \hat{A} = \sin \hat{B} \sin a$
  • The five part rule (Rule iii): $\qquad \quad \quad \; \;\sin b \cos \hat{A} = \cos a \sin c - \sin a\cos c\cos \hat{B}$
**Note:** Similar relations can be derived under circular permutation between the angles and the arcs.

**Figure A1**: Spherical triangle $STZ$
(left) Recall from Fig. 4.1.3
(right) Close-up view to the spherical triangle STZ.
The notations in red refer to the rule i), ii) and iii)

The quantity $s$, $t$, and $z$ are the arcs opposite to the vertices S, T and Z. Given the definition of these quantities and classical trigonometric identities, we can already state that:

  • $\cos s=\sin L_a$

  • $\cos t=\sin \delta$

  • $\cos z=\sin E$

Similarly, the $\sin$ of $s$, $t$ and $z$ also transform into the $\cos$ of $L_a$, $\delta$ and $E$. We will now derive each line of the transform matrix of Eq. x using the spherical trigonometry rules applies to the triangle STZ.

A.1.1 Using Rule i)

Left-hand side: $\cos b=\cos t= \sin \delta$

Right-hand side: $\cos a \cos c + \sin a \sin c \cos \hat{B}= \cos z \cos s + \sin z \sin s \cos \mathcal{A} = \sin \mathcal{E} \sin L_a + \cos \mathcal{E} \cos L_a \cos \mathcal{A}$

We have our first relationship:

$$\sin \delta = \sin \mathcal{E} \sin L_a + \cos \mathcal{E} \cos L_a \cos \mathcal{A}$$

A.1.2 Using Rule ii)

Left-hand side: $\sin b \sin \hat{A}= \sin t \sin (-H) = - \cos \delta \sin H$

Right-hand side: $\sin \hat{B} \sin a = \sin \mathcal{A} \sin z = \sin \mathcal{A} \cos \mathcal{E}$

We have our second relationship:

$$- \cos \delta \sin H = \sin \mathcal{A} \cos \mathcal{E}$$

A.1.3 Using Rule iii)

Left-hand side: $\sin b \cos \hat{A} = \sin t \cos(-H)= \cos \delta \cos{H}$

Right-hand side: $\cos a \sin c - \sin a\cos c\cos \hat{B}= \cos z \sin s - \sin z \cos s \cos \mathcal{A} = \sin \mathcal{E} \cos L_a - \cos \mathcal{E} \sin L_a \cos \mathcal{A}$

We have our last relationship:

$$ \cos\delta \cos{H} = \sin \mathcal{E} \cos L_a - \cos \mathcal{E} \sin L_a \cos \mathcal{A}$$

Rearranging in a matrix form, and correct line order, we have:

\begin{equation} \begin{bmatrix} \cos \delta \cos H\\ \cos \delta \sin H\\ \sin \delta \end{bmatrix} = \begin{bmatrix} \cos L_a \sin \mathcal{E} - \sin L_a \cos \mathcal{E} \cos \mathcal{A}\nonumber\\ \cos \mathcal{E} \sin \mathcal{A} \nonumber\\ \sin L_a \sin E + \cos L_a \cos \mathcal{E} \cos \mathcal{A} \end{bmatrix} \end{equation}
**Note:** The left hand-side of Eq. is reminiscent of the components of a base vector pointing the direction ($H$,$\delta$) in the Equatorial **XYZ** frame.
**Note 2:** This is not a coincidence (see chap. [REF])

A.2. Derivation of (l,m,n) to ($\alpha$,$\delta$)

A.2.1 Linking ($l$, $m$, $n$) to ($\alpha$,$\delta$) with spherical trigonometry

**Figure A2**: Spherical triangle $S_c S Z$
(left) Recall from Fig. 3.4.2
(right) Close-up view to the spherical triangle STZ.
The notations in red refer to the rule i), ii) and iii)

Similarly to A.1, we will derive three equations by applying spherical trigonometry identities in the triangle $\text{S}_\text{c} \text{S} \text{Z}$

\begin{eqnarray} l &=& \sin \theta \sin \psi\\ m &=& \sin \theta \cos \psi \\ n &=& \cos \theta \end{eqnarray}

and

$$l^2+m^2+n^2=1$$

A.2.1.1 Using rule i)

Left-hand side: $\cos b=\cos \theta = n$

Right-hand side: $\cos a \cos c + \sin a \sin c \cos \hat{B}= \cos (\frac{\pi}{2}-\delta) \cos (\frac{\pi}{2}-\delta_0) + \sin (\frac{\pi}{2}-\delta) \sin (\frac{\pi}{2}-\delta_0) \cos \Delta \alpha = \sin \delta \sin \delta_0 + \cos \delta \cos \delta_0 \cos \Delta \alpha$

We have our first relationship:

$$n= \cos \theta = \sin \delta \sin \delta_0 + \cos \delta \cos \delta_0 \cos \Delta \alpha$$

A.2.1.2 Using rule ii)

Left-hand side: $\sin b \sin \hat{A}= \sin \theta \sin \psi = l$

Right-hand side: $\sin \hat{B} \sin a = \sin \frac{\pi}{2}-\delta \sin \Delta \alpha = \cos \delta \sin \Delta \alpha$

We have our second relationship:

$$l = \sin \theta \sin \psi = \cos \delta \sin \Delta \alpha$$

A.2.1.1 Using rule iii)

Left-hand side: $\sin b \cos \hat{A} = \sin \theta \cos \psi= m$

Right-hand side: $\cos a \sin c - \sin a\cos c\cos \hat{B}= \cos (\frac{\pi}{2} - \delta) \sin (\frac{\pi}{2} - \delta_0) - \sin (\frac{\pi}{2} - \delta) \cos (\frac{\pi}{2} - \delta_0) \cos \Delta \alpha =\sin \delta \cos \delta_0 - \cos \delta \sin \delta_0 \cos \Delta \alpha$

We have our third relationship:

$$m=\sin \theta \cos \psi = \sin \delta \cos \delta_0 - \cos \delta \sin \delta_0 \cos \Delta \alpha$$

Let's summarize the results

\begin{eqnarray} l = \sin \theta \sin \psi &=&\cos \delta \sin \delta \alpha = (i)\\ m =\sin \theta \cos \psi &=& \sin \delta \cos \delta_0 - \cos \delta \sin \delta_0 \cos \Delta \alpha = (ii)\\ n = \cos \theta &=& \sin \delta \sin \delta_0 + \cos \delta \cos \delta_0 \cos \Delta \alpha = (iii) \end{eqnarray}

A.2.2 Expressions of ($\alpha$,$\delta$) as function of ($l$, $m$, $n$)

From the ($l$, $m$, $n$) coordinates of one source, one can compute back the ($\alpha$,$\delta$) coordinates by combinations of the $(i)$, $(ii)$, $(iii)$ relatioships.

$\require{cancel}$

\begin{eqnarray} \frac{(i)}{(ii)} &\Leftrightarrow& \frac{\cancel{\cos{\delta}} \sin\Delta \alpha}{\cancel{\cos{\delta}} \sin \delta_0 \cos\Delta \alpha} &=& \frac{l}{\sin \delta \cos \delta_0 - m}&\Leftrightarrow& \frac{\tan \Delta \alpha}{\sin\delta_0} = \frac{l}{\sin\delta\cos\delta_0-m}= (i')\\ \frac{(i)}{(iii)} &\Leftrightarrow& \frac{\cancel{\cos{\delta}} \sin\Delta \alpha}{\cancel{\cos{\delta}} \cos \delta_0 \cos\Delta \alpha} &=& \frac{l}{n-\sin \delta \sin \delta_0} &\Leftrightarrow& \frac{\tan \Delta \alpha}{\cos \delta_0}=\frac{l}{n-\sin\delta\sin\delta_0} = (ii') \\ \end{eqnarray}

$\require{cancel}$ \begin{eqnarray} (i') \sin \delta_0 = (ii') \cos \delta_0 &\Leftrightarrow & \frac{\cancel{l}\sin\delta_0}{\sin\delta\cos\delta_0 -m} = \frac{\cancel{l}\cos\delta_0}{n-\sin\delta\sin\delta_0} \\ &\Leftrightarrow& \sin\delta \cos^2\delta_0-m\cos\delta_0 = m\sin\delta_0 - \sin\delta\sin^2\delta_0 \\ &\Leftrightarrow& \sin\delta \left[ \underbrace{\cos^2 \delta_0 + \sin^2 \delta_0}_{=1} \right] = n\sin\delta_0+m\cos\delta_0 \\ &\Leftrightarrow& \boxed{\delta = \arcsin (n\sin\delta_0 + m\cos\delta_0)} \end{eqnarray}

Now, we reinject the expression of $\delta$ into $(i')$ or $(ii')$ which display a $\sin \delta$ term.

$\require{cancel}$ \begin{eqnarray} \frac{\tan \Delta \alpha}{\sin\delta_0} &=& \frac{l}{(n\sin\delta_0+m\cos\delta_0)\cos\delta_0-m} \Leftrightarrow \\ \tan \Delta \alpha &=& \frac{l \bcancel{\sin\delta_0}}{n\bcancel{\sin\delta_0}\cos\delta_0 +m \underbrace{(\cos^2\delta_0-1)}_{\sin^{\bcancel{2}}\delta_0}} \Leftrightarrow \\ \tan (\alpha - \alpha_0) &=& \frac{l}{n\cos\delta_0 + m\sin\delta_0} \Leftrightarrow \\ &\Leftrightarrow& \boxed{\alpha = \alpha_0 + \arctan \left[ \frac{l}{n\cos\delta_0 + m\sin\delta_0} \right]} \end{eqnarray}

A.3 Expression of the ($u$,$v$) ellipsis:

Starting from the expression of $u$ and $v$.

$\lambda u = X \sin H + Y \cos H$

$\lambda v= -X \sin \delta \cos H + Y \sin\delta\sin H + Z \cos\delta$

\begin{eqnarray} v &=&\frac{1}{\lambda} -X \sin \delta \cos H + Y \sin\delta\sin H + Z \cos\delta \\ \Leftrightarrow v -\frac{Z}{\lambda} \cos \delta &=& \frac{Y}{\lambda}\sin\delta\sin H - \frac{X}{\lambda} \sin\delta \cos H \\ \Leftrightarrow \frac{v -\frac{Z}{\lambda} \cos \delta}{\sin \delta} &=& \frac{Y}{\lambda}\sin H - \frac{X}{\lambda} \cos H \\ \Leftrightarrow \left[ \frac{v -\frac{Z}{\lambda} \cos \delta}{\sin \delta} \right]^2 &=& \left[ \frac{Y}{\lambda}\right]^2 \sin^2 H + \left[ \frac{X}{\lambda}\right]^2 \cos^2 H - \frac{2XY\cos H\sin H}{\lambda^2}\\ \Leftrightarrow \left[ \frac{v -\frac{Z}{\lambda} \cos \delta}{\sin \delta} \right]^2 &=& \left[ \frac{Y}{\lambda}\right]^2 + \left[ \frac{X}{\lambda}\right]^2 \underbrace{-\left[ \frac{Y}{\lambda}\right]^2 \cos^2 H - \left[ \frac{X}{\lambda}\right]^2 \sin^2 H - \frac{2XY\cos H\sin H}{\lambda^2}}_{\left[ \frac{X\sin H}{\lambda} + \frac{Y\cos H}{\lambda}\right]^2=u^2} \\ \Leftrightarrow u^2 + \left[ \frac{v -\frac{Z}{\lambda} \cos \delta}{\sin \delta} \right]^2 &=& \left[ \frac{Y}{\lambda} \right]^2 + \left[ \frac{X}{\lambda} \right]^2 \end{eqnarray}

$$\frac{u^2}{a^2} + \frac{ \left[ \frac{v -\frac{Z}{\lambda} \cos \delta}{\sin \delta} \right]^2}{a^2} = 1$$

A.4. Expressing the infinitesimal solid angle $d\Omega$ in direction cosine coordinates $(l,m,n)$

In Sec. 2.12 ➞ the infinitesimal solid angle $d\Omega$ was defined in terms of polar coordinates. The infinitesimal solid angle $d\Omega$ can also be expressed in direction cosine coordinates by using the Jacobian transformation. First the relationship between $(\theta,\phi)$ and $(l,m)$ must be established. It should be clear from Fig. A.3(b) ⤵ and Fig. A.3(c) ⤵ that: \begin{eqnarray} \phi &=& \tan^{-1}\frac{\rho m}{\rho l} = tan^{-1}\frac{m}{l}=f(l,m)\\ \theta &=& \sin^{-1}\frac{\rho \sqrt{l^2+m^2}}{\rho} = \sin^{-1} \sqrt{l^2+m^2}=g(l,m).\nonumber \end{eqnarray}

**Figure A3**: Relating $(\theta,\phi)$ and $(l,m)$.

Now by the Jacobian transformation $\boldsymbol{J}$: \begin{equation} d\Omega = \sin \theta d\theta d\phi = \sin(g(l,m)) \left| \boldsymbol{J} \right| dl dm, \end{equation} where \begin{equation} \left|\boldsymbol{J}\right|= \left| \begin{array}{cc} \frac{\delta\theta}{\delta l} & \frac{\delta\theta}{\delta m} \\ \frac{\delta\phi}{\delta l} & \frac{\delta\phi}{\delta m} \end{array} \right|, \end{equation} and \begin{eqnarray} \frac{\delta \theta}{\delta l} &=&\frac{l}{\sqrt{1-l^2-m^2}\sqrt{l^2+m^2}},\\ \frac{\delta \theta}{\delta m} &=& \frac{m}{\sqrt{1-l^2-m^2}\sqrt{l^2+m^2}},\nonumber\\ \frac{\delta \phi}{\delta l} &=& \frac{-\frac{m}{l^2}}{1+\frac{m^2}{l^2}},\nonumber\\ \frac{\delta \phi}{\delta m} &=& \frac{\frac{1}{l}}{1+\frac{m^2}{l^2}},\nonumber \end{eqnarray} so that \begin{eqnarray} \left|\boldsymbol{J}\right| &=& \frac{1}{\sqrt{1-l^2-m^2}\sqrt{l^2+m^2}(1+\frac{m^2}{l^2})}+\frac{\frac{m^2}{l^2}}{\sqrt{1-l^2-m^2}\sqrt{l^2+m^2}(1+\frac{m^2}{l^2})},\\ &=& \frac{1}{\sqrt{1-l^2-m^2}\sqrt{l^2+m^2}},\nonumber \end{eqnarray} and \begin{equation} d\Omega = \sin(g(l,m)) \left| \boldsymbol{J} \right| dl dm = \frac{dldm}{\sqrt{1-l^2-m^2}}=\frac{dldm}{n}. \end{equation}

A5. Delayed product identities of cosine and sine

The delayed product identities of cos and sin are given by: \begin{eqnarray} \cos(x-y)\cos(x) &=& \frac{1}{2}\cos y + \frac{1}{2}\cos(2x-y)\\ \sin(x-y)\sin(x) &=& \frac{1}{2}\cos y - \frac{1}{2}\cos(2x-y)\\ \sin(x-y)\cos(x) &=& -\frac{1}{2}\sin y + \frac{1}{2}\sin(2x-y)\\ \cos(x-y)\sin(x) &=& \frac{1}{2}\sin y + \frac{1}{2}\sin(2x-y). \end{eqnarray}

The delayed product identities are derived from the standard trigonometric identities. We can derive the first identiy as follow:

\begin{eqnarray} \cos(x-y)\cos(x) &=& [\cos x\cos y + \sin x \sin y]\cdot \cos x\\ &=& \cos^2 x\cos y + \cos x\sin x \sin y\nonumber\\ &=& \bigg(\frac{1+\cos 2x}{2}\bigg)\cdot \cos y + \frac{\sin 2x \sin y}{2}\nonumber\\ &=& \frac{1}{2}\cos y + \frac{\cos2x \cos y}{2} + \frac{\sin2x \sin y}{2}\nonumber\\ &=& \frac{1}{2}\cos (y) + \frac{1}{2}\cos(2x-y).\nonumber \end{eqnarray}

The remaining delayed product identities are derived similarly.